Pacifier use modifies the association between breastfeeding and malocclusion: a cross-sectional study - Catiara Terra da COSTA; Ayah Qassem SHQAIR; Marina Sousa AZEVEDO; Marília Leão GOETTEMS; Maria Laura Menezes BONOW; Ana Regina ROMANO (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract This study aimed to evaluate the influence of breastfeeding and pacifier use on the occlusal status of preschool children. A cross-sectional study was conducted with children (n = 489) aged 2-5 years in private and public schools in Pelotas, South Brazil. Mothers answered a questionnaire on demographic, socioeconomic and behavioral variables, including breastfeeding and non-nutritive sucking habits. Malocclusion was classified as normal/mild and moderate/severe, according to WHO criteria. The association between breastfeeding and pacifier use with malocclusion was tested using multivariate logistic regression. The prevalence of malocclusion was 37.83% (95%CI 33.52-42.14), and 57.87% of the children used a pacifier. A total of 46.01% of the sample was exclusively breastfed for 6 months, and 24.74% were never breastfed. Malocclusion was associated with pacifier use, and with both non-exclusively breastfed and never breastfed. After adjustments for demographic and socioeconomic variables, the children who used a pacifier and were never breastfed (OR = 19.08; 95%CI 8.54-42.63), or who used a pacifier and were not exclusively breastfed (OR = 13.74; 95%CI 6.11-30.92), showed worse occlusal conditions, compared with the children who were exclusively breastfed and never used a pacifier. Pacifier use modifies the relationship between breastfeeding and occlusal status.